Pembuatan Daftar Urut Kepangkatan Berbasis Website Di Dinas Perpustakaan Dan Kearsipan Kota Samarinda - Ricky Albin Pranata; Alief Fajar Gumilang; Aditya Pranata; Muhammad Ramadhani Saputra; Abdul Rahim (Lembaga Pengembangan Kinerja Dosen, 2024)
The Library and Archives Office of Samarinda City has not yet implemented an information system to facilitate the management of employee data and the Rank Order List. In light of this issue, we propose a solution and recommend the creation of a Rank Order List based on a website. The method we utilized for developing this website is data collection. The outcome of this community service is the successful creation of a website implemented in the Library and Archives Office of Samarinda City, eliminating the need for manual data input.